Internal carotid artery stenosis: comparison of duplex scan and magnetic resonance angiography with digital subtraction angiography - Py Marco Oliveira; André Charles; Azevedo Feliciano Silva de; Domingues Romeu Côrtes; Salomão Rodrigo Ferraz (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: We compare duplex scan (DS) and magnetic resonance angiography (MRA) with digital angiography (DGA) in respect to accuracy in measuring internal carotid artery (IC) stenosis in symptomatic patients. METHOD: Ten symptomatic patients with IC stenosis greater than 70% previously diagnosed by DS were submitted to another DS and to both MRA and DGA. Both ICs from each patient (total 20 ICs) were evaluated by physicians blinded for the results of other tests. DS and MRA were compared with DGA, using the intraclass correlation coeficient (r) and its 95% confidence interval (95% ci). For each diagnostic test, the study group (20 Ics) was also divided in surgical patients (IC stenosis between 70 and 99%) and non surgical patients, using kappa concordance coeficient (k) to compare the results. RESULTS: Main comparisons are: DS and DGA, r = 0.71 (0.4 - 0.87); MRA and DGA, r = 0.61 (0.25 - 0.82). After division into surgical vs. non-surgical groups, k = 0.857 (p < 0.0001) between DS and DGA; and k = 0.545 (p = 0.003) between MRA and DGA. Most DS and MRA errors occurred in IC sub-occlusions. CONCLUSION: The results suggest that when they are used together, DS and non-contrast MRA may substitute DGA in the evaluation of patients for IC stenosis surgery, except when there is discordance between their results or when the methods show sub-occlusive stenosis.